Diffusion couple studies of the Ni–Bi–Sn system - Gueorgui P Vassilev; Gueorgui Penev Vassilev; Nikolina Milcheva; Marie-Christine Record; Rositsa Mancheva (Journal of Mining and Metallurgy, Section B: Metallurgy, 2012)
Investigations of Ni–Bi–Sn system were performed in order to inquire the phase diagram and to assess some diffusion kinetic parameters. For this purpose diffusion couples consisting of solid nickel (preliminary electroplated with tin) and liquid Bi–Sn phase were annealed at 370 °C. Three compositions (0.8, 0.6 and 0.4 mole fractions Sn) of the Bi–Sn melts were chosen. Annealing times from 24 to 216 h were applied. The phase and chemical compositions of the contact zone were determined by means of scanning electron microscope.It was confirmed that the diffusion layers consist mainly of Ni3Sn4 but other intermetallic phases grow as well. For the first time metastable Ni–Sn phases as NiSn and NiSn8 (NiSn9) were observed in metallurgical alloys (i.e. not in electroplated samples).  The existence of a ternary compound previously reported in the literature was confirmed. More than one ternary Ni–Bi–Sn compounds might possibly be admitted.A growth coefficient of (2.29 ± 0.02) x 10-15 m2 s–1 was obtained.  It was found that the apparent activation energy for diffusion layers growth (18 ± 8 kJ mol–1) is inferior to that one assessed at growth from solid state Bi–Sn mixtures (88 ± 12 kJ mol–1).